The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1179/026708499101516425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of additives in electrolyte on characteristics of ceramic coatings formed by microarc oxidation

Abstract: The effects of adding Na2 WO4. 2H2O and SiC powder to the electrolyte on the characteristics of ceramic coatings on Al based alloys formed by microarc oxidation were studied. The ceramic coating quality was improved by the two additives, but the addition of Na2 WO4. 2H2O was more effective, as it improved the formation of Al2O3 phase in the ceramic coating, increased the ratio of the internal dense region to the whole ceramic coating, optimised the ceramic coating phase structure, and improved its wear resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…(Wei et al, 2004;Curran and Clyne, 2005a,b;Wang et al, 1999). It was reported Ma et al, 2006) that higher current density and lower solution temperature benefit film growth.…”
Section: Introductionmentioning
confidence: 92%
“…(Wei et al, 2004;Curran and Clyne, 2005a,b;Wang et al, 1999). It was reported Ma et al, 2006) that higher current density and lower solution temperature benefit film growth.…”
Section: Introductionmentioning
confidence: 92%
“…[9,10,11] The research related to development of the MAO process has intensified in the last 5 years. Voevodin and co-workers in the United States, [12] Matthews and co-workers in the United Kingdom, [13] Wang and co-workers in China, [14] Sundararajan et al in India, [15,16] and Mecuson et al in France [17] have contributed to the further development of the MAO technique in conjunction with improving our understanding of the mechanism of coating formation and coating properties. The overall wear resistance offered by the MAO coatings under the abrasion, erosion, and sliding wear modes was found to be comparable to that of the bulk alumina and better than the thermal-sprayed alumina and hard anodized coatings.…”
Section: Introductionmentioning
confidence: 95%
“…Wang et al [20] and Zheng et al [21] have found that Na 2 WO 4 could improve the formation of Al 2 O 3 phase in the ceramic coating and improve its wear resistance. Butyagin et al [22] reveal that introducing compounds of transition metals into the solution can lead to the changes in the coatings' structure, and the coatings obtained are capable of enduring higher thermocyclic loads.…”
Section: Introductionmentioning
confidence: 97%